Prevalence, Risk Factors and Complications of Preeclampsia at Rafidia Governmental Surgical Hospital in Palestine: Case-Control Study - Ali, Iyad (Jordan Journal of Pharmaceutical Sciences, 2023)
The development of hypertensive disorders is the most common medical complication during pregnancy. Preeclampsia (PE) causes multi-organ dysfunction and can lead to premature delivery, fetal death, and permanent organ damage in women. The purpose of this study is to estimate the prevalence of PE among the pregnant women who were followed at Rafidia Governmental Surgical Hospital (RGSH) in Nablus-Palestine for a year period from October 2020 to October 2021. During that period, we carried out an observational case-control study and assessed the risk factors, complications, and PE management in RGSH. The study included 170 patients with 85 preeclamptic and 85 randomly selected non-preeclamptic women from 5462 deliveries. PE group age ranged from 17 to 45 years old. PE prevalence increased with increasing gestational age (24% and 75% among women who were <37 and ≥ 37 of age, respectively), where maternal age and abortion incidents were associated with severe PE. First or multiple pregnancies were also factors linked to severe PE. Our findings support the body of evidence that PE is considered as a preventable high causative risk of fetal mortality and morbidity.